MICROPLASTIC DISTRIBUTION IN SEDIMENTS IN COASTAL OF PARIAMAN CITY, WEST SUMATERA PROVINCE - Sianturi, Kalfin; Amin, Bintal; Galib, Musrifin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
Pariaman City is a tourist destination in West Sumatra which in turn may be vulnerable to plastic waste pollution. This study was conducted in February 2020 in the coastal area of Pariaman City with the aim to determine the type and abundance of microplastic and to determine if there are any differences in the number of microplastics between stations and between depths of the sediment. The Survey method was applied and collected data from the field as well as from laboratory analysis were then analyzed and discussed. The results of the study showed that the type of microplastics found from the studied area were fragments, films, and fibres. The most common type found was fibre (59.01 %). The average abundance of microplastics at each station ranged from 178.89 – 235.56 particles/kg of dry sediment. The lowest abundance was at station 1 and the highest was at station 3. The average abundance of microplastic at 0-10 cm depth of dry sediment layer was 199.26 particles/kg and 220.00 particles/kg of dry sediment at 10-20 cm depth. ANOVA and t-test analysis showed that the quantity of microplastic between stations and between two different depths was not significantly different (p >0,05).